A parallel between the general conditions of applicability of POSDRU - POCU - Rebeca Ramona Bulzan; Roxana Herdelau (Agora International Journal of Economical Sciences (AIJES), 2016)
When we hear "POCU / POSDRU" we know that there are two funding programs carried out with the support of the European Union and the State Budget; POCU - proposed for implementation in 2014-2020, and POSDRU - implemented in 2007-2013.
Keywords: 330